None Vulnerability and Coping Capacity to Disaster Risks of Selected Barangays in Mandaon, Masbate, Philippines - Layson, Arnel V.; Legayada-Layson, Nieva (Future Science / FSH-PH Publications, 2025)
This study assessed the vulnerability and coping capacity to disaster risks of selected barangays in Mandaon, Masbate, Philippines in 2013. The study made use of a descriptive survey method wherein survey-questionnaire based on the National Disaster Risk Reduction Management Framework (NDRRMF) was used in data collection. Statistical tools included frequency count, percentage, and rank order. The data on age, gender, member per household, and income were assessed using the dependency ratio, female-to-male ratio, and poverty index. The DRRM programs implemented were analyzed by comparing them to the DRRM Framework by FAO. Results revealed that selected barangays were vulnerable to disaster risks, and the people had low coping capacity based on their age with a dependency ratio of 68.2%. In the gender component, the females are less resilient with a 1:1 ratio. In terms of income, the barangays are found to be vulnerable to the fact that 50% of the total households are found to be living below the poverty line (about 1/day/person). The programs, projects, and activities implemented by the agencies and organizations of the government are under the category of prevention, mitigation, and preparedness only based on the DRRM Framework. The barangays are also vulnerable since there are no programs yet related to response, rehabilitation, and recovery that are implemented.